RAHASIA DAGANG SEBAGAI BENTUK PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL DAN PENGATURANNYA DI INDONESIA - Widyarini Indriasti Wardani (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2011)
The enactment of Law No. 7 of 1994 on Ratification of Agreement Establishing of The World Trade Organization (Agreement of Establishing the World Trade Organization) brings the consequence that all provisions stipulated in the WTO must be complied with and implemented by Indonesia. In the WTO, GATT and TRIPS intellectual property rights protection is an important factor, and one of them is about Trade Secret. Setting these trade secrets contained in Law No. 30 year 2000 on Trade Secrets. This trade secret involves any information that must be kept from general population and have high economic value. In the practice of law, trade secret case occured in the case of Cohen vs. Lindenbaum about bribery to obtain information.